Cyberbullying: The Dynamics of Emotional Regulation in Adolescents Who Use Social Media - Sanra, S. Hashwinee; Ramadhani, Mutiara Dewi; Mirza, Rina; Pakpahan, Rosianna; Marpaung, Winida (Psikoborneo: Jurnal Ilmiah Psikologi, 2026)
The development of digital technology has influenced the social interaction patterns of adolescents and given rise to the phenomenon of cyberbullying on social media. Emotional regulation plays an important role in preventing aggressive online behavior because it is related to an individual's ability to recognize, assess, and control their emotional responses. This study aims to understand the relationship between emotional regulation and cyberbullying behavior among adolescents who use social media. The research method used a correlational quantitative approach with 100 respondents selected through purposive sampling. The research subjects consisted of 100 adolescents who use social media from Eria High School in Medan, which were determined based on the purposive sampling technique. Data analysis included normality and linearity tests, and the data were analyzed using the Pearson Product Moment correlation test with the help of IBM SPSS Statistics software edition 25. The results showed a correlation coefficient of r = -0.643 with a significance level of p = 0.000 (p < 0.05). This means that the more emotional regulation skills social media users have, the less likely they are to engage in cyberbullying. Conversely, teens with low emotional regulation tend to have a higher risk of engaging in cyberbullying behavior. Strengthening emotional regulation through character education and family support is important to prevent online aggressive behavior among teens.Perkembangan teknologi digital memengaruhi pola interaksi sosial remaja dan memunculkan fenomena cyberbullying di media sosial. Regulasi emosi berperan penting dalam mencegah perilaku agresif daring karena berkaitan dengan kemampuan individu mengenali, menilai, dan mengontrol respons emosionalnya. Studi ini bertujuan untuk memahami keterkaitan antara regulasi emosi dan perilaku cyberbullying pada remaja pengguna media sosial. Metode penelitian menggunakan pendekatan kuantitatif korelasional dengan 100 responden yang dipilih melalui purposive sampling. Subjek penelitian berjumlah 100 remaja pengguna media sosial dari SMA Eria Medan, yang dientukan berdasarkan teknik purposive sampling. Analisis data meliputi pengujian normalitas dan pengujian linieritas serta data dianalisis menggunakan uji korelasi Pearson Product Moment dengan bantuan software IBM SPSS Statistics edisi 25. Hasil penelitian memperlihatkan nilai koefisien korelasi r = -0.643 dengan tingkat signifikansi yaitu p = 0.000 (p < 0.05). Dalam artian bahwa peningkatan keterampilan regulasi emosi yang dimiliki remaja pengguna media sosial, maka makin berkurang kecenderungan mereka untuk melakukan tindakan cyberbullying. Sebaliknya, remaja dengan regulasi emosi yang rendah cenderung memiliki risiko lebih tinggi untuk terlibat dalam perilaku cyberbullying. Penguatan regulasi emosi melalui pendidikan karakter dan dukungan keluarga penting dilakukan untuk mencegah perilaku agresif daring di kalangan remaja.